Model-Based Seismic Inversion to Delineate Tight Carbonate Reservoirs, Dhulian Area, Upper Indus Basin, Pakistan - Arshad, Z.; Shakir, U.; Hussain, M. (The Nucleus, 2022)
Development of new technologies and integration concepts are required for remunerative exploration and effective exploitation of hydrocarbons. Seismic inversion is one of these latest techniques which allows accurate prediction of reservoir litho-facies and distribution of petrophysical properties (e.g., clay volume and porosity) within intricate corridors. Seismic inversion is a technique that brings out purposeful information from seismic data for reservoir characterization. In this study, an effort has been made to establish a correlation between the conventional method for exploration of hydrocarbons and post-stack model-based seismic inversion. The research work done on Dhulian area mainly exhibits complex features due to the compressional regime. Petrophysical analysis has indicated reservoir formations at the level of Paleocene and Eocene formations and has shown fair potential of hydrocarbon accumulation in Sakesar Limestone as compared to other zones. Structure studied through geology and literature review is popup anticline with thrust faults which is also clearly delineated on seismic data. Seismic Attribute analysis provides a clearer image of the subsurface, highlighting reservoir qualities and indicating the presence of hydrocarbons at the level of Paleocene and Eocene formations. Contour maps and 3D depth maps show structure is deepening towards North-East and is shallow in South-West. Estimated porosities from seismic inversion also give adequate limestone porosities for Sakesar Limestone to be a reservoir. Geo-statistical analysis is applied to establish a relationship between well-log data and seismic data to study rock properties and has shown a good correlation coefficient between them.